Perbedaan Peningkatan Kemampuan Representasi Matematis Siswa PBL Berbantuan Geogebra dan DL Di Kelas X SMA - Angga Dinata; Muhammad Amin Fauzi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to understand the impact of problem-based learning (PBL) on mathematical representation in students using Geogebra and model discovery learning in X SMAS Tamansiswa Singosari. It uses quasi-experimental research with purposive sampling and control group design. The results show that all data is normal and homogeneous, with a value of 4.71>2.03. The study also reveals that the overall learning process for experimental students is better than that of control students.